A primary source guide to Ireland - Rose, Elizabeth, 1970- (New York : PowerKids Press, 2004)
Describes the geography, people, history, government, economy, and culture of Ireland.
The Emerald Isle -- Soft weather -- Early Irish history -- Ireland and Northern Ireland -- The Irish government -- Ireland's economy -- Religion in Ireland -- The writers of Ireland -- Ireland today -- Ireland at a glance.
Includes index.
6.3
3-6
Keywords: Ireland -- Juvenile literature; Ireland; Ireland